PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION: UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KREATIF, AKTIVITAS DAN RESPON SISWA SMP - Fathimah Az.Zahrah Nasiruddin; Erni Ekafitria Bahar; Haerul Syam; Sri Rahayuningsih (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Many researchers, especially mathematics education research, are increasingly focusing on mathematical creativity. From the observations of researchers at the Guppi Samata Middle School, Kab. Gowa indicated that students' mathematical creative thinking skills were relatively low and far from expectations. One aspect that is needed to improve students' creative thinking skills is to provide a learning atmosphere that is able to stimulate students through activities of reasoning, creating, problems solving, constructing and applying. This type of research is a pre-experimental research aimed at improving students' creative thinking skills, activities and responses through the application of Auditory Intellectually Repetition learning. The results showed that there was an increase in students' creative thinking skills, activities and responses after the implementation of Auditory Intellectually Repetition learning. Researchers suggestions related to the results of the study, it is hoped that further researchers will develop an AIR learning model according to the characteristics of junior high school students